Risk for molar incisor hypomineralization in children with hypomineralizations in the deciduous dentition: a case-control study on children from a Swiss suburban region - Andrea Stefanie Manz; Dieter Müssig; Florian Wegehaupt; Thomas Attin; Philipp Sahrmann (BMC Oral Health)
Abstract Objectives A possible co-occurence of hypomineralizations in deciduous teeth (HD) and Molar Incisor Hypomineralization (MIH) is matter of ongoing discussion. This case control study aimed to assess whether there was a correlation between HD and MIH in a suburban Swiss population. Methods Patients were seen once at the age of 4–6 and a second time at 8–9 years, each, for comprehensive dental examination, including the diagnosis of HD and MIH. Appointments took place as part of routinely annual examinations in a school dental clinic of the municipality of Uster. In a retrospective approach, children with hypomineralizations in the deciduous dentition at the first appointment were defined as “cases”. An identical number of age- and gender-matched “controls” without hypomineralizations were randomly chosen from the patient files. The odds ratio for MIH - as reported during the second appointment - for cases with HD compared to controls without was calculated using chi-square, quota ratio and Fisher’s exact test with a level of significance of 0.05%. Results In the cohort of 426 children (112 females and 101 males in each group) the overall prevalence of MIH was 11.7%, with mainly mild signs of MIH. Case patients showed 1.24 ± 0.70 teeth with HD. For the test group, the odds ratio for MIH was 1.44 as compared to the controls, failing to show statistical significance. Conclusion There might be a slightly enhanced probability for MIH if the deciduous dentition display hypomineralizations. Clinical significance Given hypomineralizations in the deciduous dentition, the probability for Molar Incisor Hypomineralizations might be slightly enhanced.